Topological zones define basolateral amygdala synaptic input and functional organization of the claustrum - Ham, Gao Xiang (Nanyang Technological University, 2022)
The claustrum (CLA) is a highly connected brain structure whose function is largely unknown. Given the prominent role of the basolateral amygdala (BLA) in emotional processing and valence coding, understanding the functional relationship between the CLA and the BLA may provide important insights into claustral function. I used viral-based tracing techniques, optogenetics and brain slice electrophysiology to dissect the circuit relationships between the BLA and the CLA. I uncovered a unique ring-like innervation of the CLA shell – but not the CLA core – by BLA axons. Although BLA inputs to both CLA regions were similar – mostly excitatory, weak and variable, differences in intrinsic excitability and action potential dynamics suggests potential differences in BLA input processing. M1-projecting and RSC-projecting claustral neurons exhibited differences in both their intrinsic electrical properties and their BLA input. In addition, retrograde tracing of M1-, RSC- and BLA-projecting claustral neurons revealed localization of these neurons into distinct claustral subregions, as well as unique projection networks with clear functional trends. My findings establish that the claustrum can be topologically separated into at least 3 distinct functional regions, which differ not only in their input sources, but also their projection networks, intrinsic electrical properties and, in some cases, BLA innervation. These findings represent a fundamental step toward understanding how the BLA regulates CLA activity and illuminates fundamental organizational principles of claustral network connectivity.